Practical guide to ICP-MS : a tutorial for beginners - Thomas, Robert, 1949- (Boca Raton : Taylor & Francis, 2013)
"Presenting an in-depth discussion of the fundamental principles, analytical advantages, and practical capabilities of ICP-MS, this volume offers key concepts in a reader-friendly format suitable for those with limited knowledge of the technique. Written by an insider with more than 20 years experience in product development, customer support, and technical marketing for an ICP-MS instrument vendor, the book highlights this powerful ultra trace-element technique as a practical solution to real-world problems. The new edition has been updated and revised to cover new developments and updates to existing applications and reflects the significant new technology introduced by vendors since the second edition published"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Inductively coupled plasma mass spectrometry; Electronic books